The Role of Ethnomathematics Based on Traditional Engklek Games in Improving the Ability to Understand Mathematical Concepts Sipirok Muhammadiyah Elementary School Students - Nur Sahara; Fitriani Fitriani (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2022)
This study aims to determine the effectiveness of the role of ethnomatematics based on traditional crank game in increasing the ability of students to understand mathematical concepts at SD Muhammadiyah Sipirok and their responses to learning. This type of research is qualitative research. The learning model developed is a type of traditional game where elementary school students will be more enthusiastic about learning mathematics, especially in flat shape material where the concepts used will improve students' understanding of mathematical concepts. From the results of the analysis of observations during the learning process and the results of interviews conducted by comparing the tcount and ttable values ​​that the calculated value is greater than the table value and the results of the questionnaire students' responses to learning with the use of ethnomatematics based on traditional crank games are already in the very happy category because each None of the students scored 30 below or obtained half the expected maximum score of 60 where all students were above 30. The results of the research will be the type of flat shape in the crank game, the problem of the suitability of the crank game with the flat shape material and its understanding, the flat shape is used as contextual learning.